PERBEDAAN HASIL BELAJAR EKONOMI DENGAN MENGGUNAKAN METODE KOOPERATIF JIGSAW DAN METODE KONVENSIONAL PADA SISWA KELAS X SMA N 6 PADANG - Mariza, Lena; Armiati, Armiati; Ramayani, Citra (Pendidikan Ekonomi, 2013)
ABSTRAKThis study aims to analyze economic differences in learning outcomes of students who use the jigsaw method of cooperative learning with conventional learning method on economic subjects class X SMA Negeri 6 Padang. This research is a research experiment. The study population was all students in the class X SMA Negeri 6 Padang listed on the Academic Year 2013/2014 a number of 291 students. The second sample was selected using purposive sampling techniques that can number in the sample of 32 students in the experimental class and 32 students in the control class. Types of data from this study are primary and secondary data. Techniques of data analysis is descriptive analysis and inductive analysis , the main data of this penlitian obtained from test results to learn both classes are conducted through a sample Z test using the test for normality and homongenitas grade sample variance with SPSS version 15. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples .Hypothesis test results obtained Zhitung was 3,508 while 1,960 Ztabel is that it looks bigger than Ztabel Zhitung, means tested hypothesis (Ha ) is accepted at the 5 % significance level alfha so his decision is H0 is rejected and Ha accepted so it can be concluded that there is a difference economic learning outcomes of students using cooperative learning jigsaw with the conventional method in class X SMA Negeri 6 Padang. From the results of this study are expected to teachers to implement jigsaw method of cooperative learning for material that is the theory . This jigsaw cooperative learning can improve student learning outcomes so that problems that occur in the learning process can be overcome Â Keywords: Learning Outcomes, jigsaw cooperative learning methods, conventional methods